Influence of inflammation factors on indices of vegetative tone in children with recurrent respiratory diseases - L.S. Ovcharenko; D.N. Sheludko (Zaslavsky O.Yu., 2018)
Among children of school age, respiratory diseases rank first in the structure of the overall morbidity, their prevalence is more than 60 %. Often, frequent episodes of respiratory pathology determine to the formation of recurrent forms, which is a strong reason for the absence of active games and outdoor walks, skipping school and increasing the time spent with mass communication tools and electronic games leading to the formation of hypodynamia and increased psychoemotional stress and, in turn, to a negative impact on the functioning of the regulatory systems of the child's body. Recurrent upper respiratory infections (acute respiratory diseases - ARI) lead to the stress of neuroendocrine immune regulation causing an imbalance of neuropeptides - mediators of neurogenic inflammation. The aim of this work is to study the indices of neurogenic inflammation in primary school pupils with recurrent pathology of the respiratory tract. An increase in the serum content of substance P was detected in schoolchildren with recurrent ARI, which had statistically significant differences with the indices of apparently healthy children (p < 0.05). It was found that increased concentration of substance P increases the risk of recurrent diseases. It has been proved that in children with recurrent ARI due to an increased serum level of NO final stable metabolites, which have a proinflammatory orientation, the activity of neurogenic inflammation increases. It was found that a significant decrease in the content of vasoactive intestinal peptide as an anti-inflammatory transmitter in children with recurrent ARI cannot inhibit the activity of neurogenic inflammation leading to its excessive stimulation.